The long-circulating effect of pegylated nanoparticles revisited via simultaneous monitoring of both the drug payloads and nanocarriers - Wufa Fan; Haixia Peng; Zhou Yu; Luting Wang; Haisheng He; Yuhua Ma; Jianping Qi; Yi Lu; Wei Wu (Elsevier, 2022)
The long-circulating effect is revisited by simultaneous monitoring of the drug payloads and nanocarriers following intravenous administration of doxorubicin (DOX)-loaded methoxy polyethylene glycol-polycaprolactone (mPEG-PCL) nanoparticles. Comparison of the kinetic profiles of both DOX and nanocarriers verifies the long-circulating effect, though of limited degree, as a result of pegylation. The nanocarrier profiles display fast clearance from the blood despite dense PEG decoration; DOX is cleared faster than the nanocarriers. The nanocarriers circulate longer than DOX in the blood, suggesting possible leakage of DOX from the nanocarriers. Hepatic accumulation is the highest among all organs and tissues investigated, which however is reversely proportionate to blood circulation time. Pegylation and reduction in particle size prove to extend circulation of drug nanocarriers in the blood with simultaneous decrease in uptake by various organs of the mononuclear phagocytic system. It is concluded that the long-circulating effect of mPEG-PCL nanoparticles is reconfirmed by monitoring of either DOX or the nanocarriers, but the faster clearance of DOX suggests possible leakage of a fraction of the payloads. The findings of this study are of potential translational significance in design of nanocarriers towards optimization of both therapeutic and toxic effects.